Developing Teachers’ Professional Learning: Canadian Evidence and Experiences in a World of Educational Improvement - Campbell, Carol (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
This article discusses the current international emphasis on educational improvement and, particularly, approaches to developing teachers’ professional learning. I begin by arguing for the importance of Canadian narratives and evidence within global debates. I turn then to an example of a recently conducted study of the state of educators’ professional learning in Canada to examine research-informed principles and examples from policies and practices across Canada. I conclude by arguing for the importance of the Canadian education community learning with, from, and for Canada, appreciating that diversity is our strength, but recognizing that inequities are our greatest challenge.